2020
DOI: 10.12775/jehs.2020.10.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Use of mobile phones by youth regarding the potential health consequences – a survey study

Abstract: Use of mobile phones by youth regarding the potential health consequences-a survey study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Similarly, our study revealed that mobile phone ownership was linked to having a more thorough HIV/AIDS understanding than lack of it. Mobile phones have recently become a signi cant part of people's daily lives, and they are especially appealing to the youth [44,45]. It is said to have been gradually overtaking 'traditional media' such as television [46].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our study revealed that mobile phone ownership was linked to having a more thorough HIV/AIDS understanding than lack of it. Mobile phones have recently become a signi cant part of people's daily lives, and they are especially appealing to the youth [44,45]. It is said to have been gradually overtaking 'traditional media' such as television [46].…”
Section: Discussionmentioning
confidence: 99%